Creative Mathematics: video production with 5th year Elementary School Students - Oliveira, Carloney Alves de; Portela, Márcia da Silva Santos; Melo, Wilker Araújo de (Educação Matemática Debate, 2025)
The study investigated the production of digital videos for teaching quantities and measurements in the 5th grade of Elementary School. Using a qualitative approach and intervention research, the active participation of students in the creation of videos that related mathematical concepts to everyday life, such as measurements in supermarkets, was analyzed. The experience favored active learning, promoting engagement, creativity, and the development of abilities such as communication, teamwork, and critical thinking. The videos facilitated the understanding of the content and made learning more dynamic. Despite the challenges in organization and editing, students highlighted the importance of collaboration. It is concluded that audiovisual production, in a participatory approach, is an effective resource for making mathematics teaching more accessible and meaningful.